2018
DOI: 10.1161/circheartfailure.118.004969
|View full text |Cite
|
Sign up to set email alerts
|

Chronotropic Incompetence in Chronic Heart Failure

Abstract: Chronotropic incompetence (CI) is generally defined as the inability to increase the heart rate (HR) adequately during exercise to match cardiac output to metabolic demands. In patients with heart failure (HF), however, this definition is unsuitable because metabolic demands are unmatched to cardiac output in both conditions. Moreover, HR dynamics in patients with HF differ from those in healthy subjects and may be affected by β-blocking medication. Nevertheless, it has been demonstrated that CI in HF is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 92 publications
4
67
0
3
Order By: Relevance
“…Moreover, chronotropic response as an extra input feature contributed to the ability to predict functional capacity in the CR population. This is in line with previous studies, which have already shown that chronotropic response is a significant predictor of training response during a CR program [35,36]. If CR is moved to an in-home setting, proper context interpretation is necessary.…”
Section: Linear and Nonlinear Regression Modelssupporting
confidence: 90%
“…Moreover, chronotropic response as an extra input feature contributed to the ability to predict functional capacity in the CR population. This is in line with previous studies, which have already shown that chronotropic response is a significant predictor of training response during a CR program [35,36]. If CR is moved to an in-home setting, proper context interpretation is necessary.…”
Section: Linear and Nonlinear Regression Modelssupporting
confidence: 90%
“…An association between CI and HF was recently reviewed. 19 CI is a heterogeneous phenotypic diagnosis with multiple associated etiologic causes, such as HF and pharmacologic therapy. 8 , 13 As there are multiple methods of assessment and detection of CI, the incidence, prevalence, and even definitions of CI vary widely.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism underlying this association has yet to be determined, we postulated that it may be similar to the mechanism of chronotropic incompetence. Chronotropic incompetence is defined as the inability to adequately increase heart rate during exercise to match cardiac output to metabolic demands and is associated with poor exercise tolerance and high mortality rate 28,29 . Autonomic dysfunction has been reported to be responsible for chronotropic incompetence 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronotropic incompetence is defined as the inability to adequately increase heart rate during exercise to match cardiac output to metabolic demands and is associated with poor exercise tolerance and high mortality rate. 28,29 Autonomic dysfunction has been reported to be responsible for chronotropic incompetence. 30 We measured pupil area after dark adaptation in this study, and the pupils commonly dilate in the dark because of appropriate autonomic nervous activity.…”
mentioning
confidence: 99%